PENERAPAN METODE BALANCE SCORECARD SEBAGAI ALAT ANALISIS PENGUKURAN KINERJA PERUSAHAAN - Syifatulloh, Wulandari Nur; Hirawati, Heni (JAB (Jurnal Akuntansi & Bisnis), 2020)
The objectives of this study are: (1) measuring the performance of PD. BPR Bank Bapas 69 Magelang by using a performance measurement method that not only measures financial performance but also non-financial namely the Balanced Scorecard which includes financial perspective, customer perspective, internal business perspective, and growth perspective and learning, (2) motivate employees to improve their performance, and (3) provide an overview of the extent of the performance of PD. BPR Bank Bapas 69 and what aspects can be improved related to the four perspectives analyzed. The population in this study are customers and employees or the public who use services or products from PD. BPR Bank Bapas 69 while for the sample in this study were 42 employees and customers or consumers of PD. BPR Bank Bapas 69 with the sampling method is the simple random sampling method. This study uses a case study method in which data taken comes from financial reports and other reports relating to the measurement of the balance scorecard in the 2016-2018 period. The results of this study indicate that in general the performance of PD. BPR Bank Bapas 69 position is quite good from the perspective of the Balanced Scorecard.Â Â Keywords: Balance scorecard, Performance